The potential clogging and filter performance of selected geotextiles with different soil types under unidirectional flow conditions in sub-soil drainage applications - Van Rooy, J.L. (Jan Louis) (University of Pretoria, 2022)
Dissertation (MSc (Engineering Geology))--University of Pretoria, 2022.